2010
DOI: 10.1088/1742-5468/2010/01/l01001
|View full text |Cite
|
Sign up to set email alerts
|

Walkers on the circle

Abstract: We experimentally demonstrate that the statistical properties of distances between pedestrians which are hindered from avoiding each other are described by the Gaussian Unitary Ensemble of random matrices. The same result has recently been obtained for an n-tuple of non-intersecting (one-dimensional, unidirectional) random walks. Thus, the observed behavior of autonomous walkers conditioned not to cross their trajectories (or, in other words, to stay in strict order at any time) resembles non-intersecting rand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(31 reference statements)
0
5
0
1
Order By: Relevance
“…arXiv:1207.0832v2 [physics.soc-ph] 23 Oct 2012 Seyfried et al [4,9,10] have performed experiments with pedestrians following an oval path. Similar studies have been reported in references [11,12]. These experiments have been performed either by using video analysis of the individual trajectories along one straight portion of the set-up [10], or by measuring times at which each participant passes a given measuring point [12].…”
Section: Introductionmentioning
confidence: 99%
“…arXiv:1207.0832v2 [physics.soc-ph] 23 Oct 2012 Seyfried et al [4,9,10] have performed experiments with pedestrians following an oval path. Similar studies have been reported in references [11,12]. These experiments have been performed either by using video analysis of the individual trajectories along one straight portion of the set-up [10], or by measuring times at which each participant passes a given measuring point [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such experiments have indeed already been performed in the past. In [12], the distribution of time headways was measured. Seyfried et al [13] have measured the density and velocity of pedestrians following an oval trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Pedestrian traffic flow has been studied empirically in a wide variety of situations, using both experimental methods and motion tracking of real crowds. The simplest case is uni-directional flow in a corridor, in which properties such as the dependence of speed on density have been analyzed [19][20][21][22][23][24]. Collision avoidance between pedestrians has been investigated in pairs of walkers [25,26] and multiple walkers [27].…”
Section: Introductionmentioning
confidence: 99%